Impact of Fluorescent in Situ Hybridization Aberrations and CLLU1 Expression on the Prognosis of Chronic Lymphocytic Leukemia: Presentation of 156 Patients From Turkey - Abur, Ü.; Ogǔr, G.; Akar, Ö.S.; Altundaǧ, E.; Aymelek, H.S.; Özatli, D.; Turgut, M. (Turkish Society of Hematology, 2018)
Objective: This study evaluates the impact of CLLU1 expression and fluorescent in situ hybridization (FISH) analysis of a group of Turkish chronic lymphocytic leukemia (CLL) patients. Materials and Methods: A total of 156 CLL patients were analyzed by FISH method; 47 of them were also evaluated for CLLU1 expression. Results were correlated with clinical parameters. Results: FISH aberrations were found in 62% of patients. These aberrations were del13q14 (67%), trisomy 12 (27%), del11q22 (19%), del17p (8%), and 14q32 rearrangements (20%). Overall del11q22 and del17p were associated with the highest mortality rates, shortest overall survival (OS), and highest need for medication. Homozygous del13q14, 14q32 rearrangements, and higher CLLU1 expression correlated with shorter OS. Conclusion: Cytogenetics/FISH analysis is still indicated for routine evaluation of CLL. Special consideration is needed for the poor prognostic implications of del11q22, del17p, 14q32 rearrangements, and homozygous del13q14. The impact of CLLU1 expression is not yet clear and it requires more data before becoming routine in genetic testing in CLL patients. © 2018 by Turkish Society of Hematology.
Kronik Lenfositik Lösemi Hastalarının Prognozunda Floresan in Situ Hibridizasyon Aberasyonları ve CLLU1 Ekspresyonunun Etkisi: Türkiye’den 156 Hastanın Sunumu
Keywords: Chronic Leukemia; Chronic Lymphocytic Leukemia; CLLU1; Cytogenetics/FISH